2008
DOI: 10.1002/ijc.23898
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase induces VEGF C and facilitates tumor lymphangiogenesis

Abstract: Heparanase is an endoglycosidase that specifically cleaves heparan sulfate side chains, a class of glycosaminoglycans abundantly present in the extracellular matrix and on the cell surface. Heparanase activity is strongly implicated in tumor angiogenesis and metastasis attributed to remodeling of the subepithelial and subendothelial basement membranes. We hypothesized that similar to its proangiogenic capacity, heparanase is also engaged in lymphangiogenesis and utilized the D2-40 monoclonal antibody to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 46 publications
3
90
1
2
Order By: Relevance
“…Although experimental studies that identify the function of HPA in promoting the secretion of VEGF are poorly reported, melanoma, breast and prostate cancer cells with overexpression of HPA cause the level of VEGF-C to increase by 3-5 times, and promote angiogenesis of transplant tumors. Conversely, the silencing of HPA genes reduces the VEGF-C level (32). The present study revealed that the expression level of HPA in primary lesions of cervical cancer patients with LN metastasis was notably higher than that in non-metastatic cases, which supports the hypothesis that HPA promotes LN metastasis from the point of view of clinicopathology.…”
Section: Discussionsupporting
confidence: 85%
“…Although experimental studies that identify the function of HPA in promoting the secretion of VEGF are poorly reported, melanoma, breast and prostate cancer cells with overexpression of HPA cause the level of VEGF-C to increase by 3-5 times, and promote angiogenesis of transplant tumors. Conversely, the silencing of HPA genes reduces the VEGF-C level (32). The present study revealed that the expression level of HPA in primary lesions of cervical cancer patients with LN metastasis was notably higher than that in non-metastatic cases, which supports the hypothesis that HPA promotes LN metastasis from the point of view of clinicopathology.…”
Section: Discussionsupporting
confidence: 85%
“…The clinical analyses suggested that heparanase facilitates tumor lymphangiogenesis which is mediated, possibly, by VEGF-C gene induction [9]. We also found that heparanase and VEGF-C mRNA expression did not correlate with the pathological type and grade of the tumor (P>0.05); it contradicts the view of correlation between tumor metastasis and pathological type or degree of differentiation.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have demonstrated that overexpression of heparanase in human tumours, including bladder cancer, facilitates their invasive activity [16]; heparanase and VEGF-C (vascular endothelial growth factor-C, a lymphatic molecular player) co-expression is related with the occurrence of lymphangiogenesis [17].…”
Section: Introductionmentioning
confidence: 99%